PENINGKATAN HASIL BELAJAR MATEMATIKA PENGUKURAN SUDUT MELALUI MODEL PROBLEM BASED LEARNING DENGAN MEDIA JAM SUDUT PADA PESERTA DIDIK KELAS V SD - Wulandari, Tri Mei; Arief Cahyo Utomo; Tri Undari, S.Pd (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the low learning outcomes of fifth grade students of Beskalan No. 14 Surakarta Elementary School. Therefore, a learning model and media are needed to improve learning outcomes and understanding of angle measurement material. The purpose of this study is to improve mathematics learning outcomes of angle measurement material for fifth grade students of Beskalan No. 14 Surakarta Elementary School using the Problem Based Learning (PBL) model and angle clock media. This research is a Classroom Action Research (CAR) consisting of 2 cycles, each cycle is a series of activities each consisting of 4 stages, namely planning, implementation, observation, and reflection. The subjects in this study were 14 fifth grade students of Beskalan No. 14 Surakarta Elementary School consisting of 8 male students and 6 female students. To determine the implementation of Mathematics learning of angle measurement material using the Problem Based Learning (PBL) model with angle clock media. From the 2 cycles, the first cycle obtained 6 students who completed and 8 students had not reached the Minimum Completion Criteria (KKM). The second cycle obtained an increase to 100% of students who completed their studies. From the research that has been done, it can be concluded that the use of the Problem Based Learning learning model with the angle clock media can improve student learning outcomes in Mathematics learning on angle measurement material for grade V students of Beskalan Elementary School No. 14 Surakarta. In addition, student learning is more meaningful, making students learn to better understand the angle measurement material based on the results of their learning experiences, fun, active and enthusiastic.